2012
DOI: 10.1111/j.1835-2561.2011.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Policies in the Extractive Industry: A Global and a Turkish Perspective

Abstract: This paper investigates the influence of accounting standards on financial reporting for companies in the extractive industry. In Turkey, listed firms have prepared their financial reports according to the International Accounting Standards and the International Financial Reporting Standards (IAS/IFRS) since 2005, as has the European Union. The aim of this study is to determine the degree of compliance with IFRS 6, comparing global and Turkish extractive entities. We find that the entities reporting in accorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Smaller and premature companies prefer FC methods, and larger and well‐established companies prefer the SE method (see Karapinar et al. ). Second, changing accounting methods for established extractive companies comes at a significant cost (Nobes and Perramon ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Smaller and premature companies prefer FC methods, and larger and well‐established companies prefer the SE method (see Karapinar et al. ). Second, changing accounting methods for established extractive companies comes at a significant cost (Nobes and Perramon ).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that IFRS 6 simply codifies the current industry accounting practices and provides much flexibility to extractive companies in choosing the reporting method as they see fit; Karapinar et al. () concur. Cortese et al.…”
Section: Similar Studiesmentioning
confidence: 99%
See 3 more Smart Citations